THE SUSPENSION OF DETENTION TO DEFENDANT IN PADANGSIDIMPUAN DISTRICT COURT - Zulkarnain Hasibuan; Syahril Syahril (Law Faculty of Universitas Bandar Lampung, 2025)
In the series of criminal justice proceedings, the issue of detention is one of the most essential matters concerning the freedom of human rights, because every detention of a person suspected of being involved in a criminal incident is a temporary restraint on his freedom and ndependence. So that in this study the problems are, first, whether the implementation of the provision of guarantees, whether in the form of people or money, has been carried out in accordance with the provisions of the legislation? Second, what are the judges' considerations in granting detention postponements for defendants within the jurisdiction of the Padangsidimpuan District Court? The methods used are library research and field research. After the data was analyzed using hypothesis testing techniques based on induction and deduction methods. Then it can be concluded that if we look at the developments in the practice of granting bail in the jurisdiction of the Padangsidimpuan District Court as stipulated in Article 31 paragraph (1) of the Criminal Procedure Code, then in determining whether or not the request for bail with a guarantee submitted by the suspect or defendant to the detaining agency can be granted.